1979
DOI: 10.1111/j.1745-6606.1979.tb00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction/Dissatisfaction with Food Shopping Among Elderly Consumers

Abstract: The food shopping behavior of 110 elderly households in a standard metropolitan statistical area was examined. Data were collected by personal interview concerning the shopping behavior problems of elderly consumers and the frequency and types of dissatisfaction with food products purchased. Implications and directions for further research are suggested for those concerned with the role of the elderly in the marketplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 16 publications
2
30
0
1
Order By: Relevance
“…This has been used by researchers to investigate the quality in food shopping with a cross-section of consumer groups (Bell et al, 1997) and, more specifically, with elderly people in the USA to identify problem areas (Mason and Bearden, 1979). One of the main theories of consumer satisfaction is Expectancy Disconfirmation Theory (Oliver, 1980), which explains consumer satisfaction as a series of evaluations of performance with expectations.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been used by researchers to investigate the quality in food shopping with a cross-section of consumer groups (Bell et al, 1997) and, more specifically, with elderly people in the USA to identify problem areas (Mason and Bearden, 1979). One of the main theories of consumer satisfaction is Expectancy Disconfirmation Theory (Oliver, 1980), which explains consumer satisfaction as a series of evaluations of performance with expectations.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These aspects are not unique to US consumers and many of the difficulties are the same as for UK consumers. Leighton et al (1996) and Leighton and Seaman (1997) found that reaching high and low shelves, carrying baskets and reading price displays were the areas that caused most difficulty when shopping Suggestions on how to rectify these problems and market to older consumers have been identified by several authors (Wallis, 1994;Lambert, 1979;Mason Downloaded by University of York At 04: 36 11 June 2016 (PT) Expectations of older food consumers 217 and Bearden, 1979), although these problem areas have existed for many years and are summarised in the following list (adapted from Mason and Bearden, 1979;Wallis, 1994):…”
Section: Causes Of Dis/satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason Pan and Zinkhan (2006) call for a stronger research focus on the question 'Why do older people shop where they do?' A deeper understanding of the store format patronage behaviour of this particular consumer segment would ultimately enable retailers to take the specific needs of elderly consumers into account in their operations (Mason and Bearden 1979). This is particularly true for grocery shopping -a frequent and challenging task in older consumers' lives (Whelan et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The relevance and necessity of looking at cognitive age in the context of older consumers is to understand how changes due to aging (Moschis, 1994) -better reflected by self-perceived age than chronological age -influence perceptions and ultimately behaviour related to store-based shopping. Ultimately, a deeper understanding of age-related changes in store patronage will enable retailers to take the special needs of elderly consumers into account in their marketing and operations (Mason & Bearden, 1979). As such, an in-depth look into the role of cognitive age in terms of store patronage behaviour could help to overcome a recognised problem in retail management and marketing, that 'painting all elderly consumers with the same broad brush because of their age eliminates much of their individual complexity and does not allow for meaningful market segmentation' (Gwinner & Stephens, 2001, p. 1032.…”
Section: Introductionmentioning
confidence: 99%